Basaltic Lava Characteristic in Goa Pandan Area, Sukadana, East Lampung: Inferences from Stratigraphy and Petrography Analysis - Happy Christin Natalia Sirait; Bilal Al Farishi; Nono Agus Santoso; Andreas Maruli Pakpahan; Hissy Ijitiha Sari; Angga Jati Widiyatama; Risky Martin Antosia (UIR PRESS, 2023)
The presence of extensive basalt formations in East Lampung has its own attractions in the field of geology, particularly the presence of Goa Pandan as a lava cave and tourist attraction in East Lampung. The presence of basalt lava in the southern part of the South Sumatra Basin has drawn attention to the presence of this lava, but detailed research on the characteristics of the lava and its formation process is still very rare. This study aims to determine the eruption period of the basalt lava and magma evolution process based on the correlation between lava stratigraphy and petrography analysis. Field observations show a lava sequence that forms Goa Pandan. Each lava sequence is characterized by autobreccia and vesicular structures on the surface. In addition, the presence of columnar joints, sheeting joints, massive lava, and other additional structures indicate the characteristics of low-viscosity basalt lava. The presence of mineral structures and abundance under the microscope clearly shows the magma formation process when basalt lava flowed on the surface. Resorption-overgrowth of plagioclase and pyroxene minerals indicates an open system when basalt lava flowed on the surface. In addition, the presence of zoning and patching in plagioclase minerals indicates that magma variability is influenced by temperature. The documentation of this lava stratigraphy can serve as a basis for further understanding of magma characteristics and formation processes. There is still much geological work that can be done in the research area to get a detailed picture of the evolution process of magma and the presence of basalt lava in this area.